Співвідношення основних фракцій ліпідів у жовчі щурів при дії тестостерону - Чернуха, Ірина; Решетнік, Євдокія; Весельський, Станіслав; Макарчук, Микола; Chernuha, Iryna; Reshetnik, Evdokia; Nurishchenko, Natalya; Veselsky, Stanislav (Східноєвропейський національний університет імені Лесі Українки, 2017)
У гострих дослідах на щурах-самцях із канюльованою жовчною протокою, які перебували під тіопента- ловим наркозом (60 мг/кг), установлено, що ефективність дії внутрішньопортально введеного тестостерону пропіонату (0,7 мг/кг) проявляється поступово й тільки через 2–2,5 год реєструються достовірні суттєві зміни у співвідношенні основних фракцій ліпідів у жовчі піддослідних тварин, порівняно з контролем. У зв’язку з широким застосуванням препарату тестостерону пропіонату та з огляду на виявлені його ефекти на ліпідний склад жовчі при одноразовому внутрішньопортальному введенні доцільно дослідити вплив курсового застосування цього препарату на характеристики зовнішньосекреторної функції печінки. It is known that androgens play a significant role in the pathogenesis of hepatic steatosis and in the regulation of lipid metabolism and bile secretory function of liver. Lipids are important components of mammalian bile. Bile lipids play a substantial role in the formation of colloidal and micellar structure of the bile. Bile lipids may exhibit cytoprotective properties in the liver damage conditions. Evaluate the influence of androgens on bile secretion function and such an important component of bile formation as lipids secretion can be studied the effects of the hormone on the content of various lipid components in bile. The aim of our study is to investigate the effect of testosterone on lipids ratio in bile male rats. The study was conducted on white male rats weighing 0,18.0,23 kg. In acute experiments, the animals were administered as an anesthetic thiopental sodium 60 mg / kg, then cannulated bile duct and, after selection the first halfhour sample of bile, injected with testosterone propionate (0,7 mg / kg, intraportal) and collected the next five half-hour samples of bile. The concentrations of the phospholipids, cholesterol, free fatty acids, triglycerides, cholesterol esters in the bile samples were determined by TLC. Statistical analysis of the results was performed using the package Statistica 7,0 (Stat Soft, USA) taking into account the criteria t-Student. Normality of data distribution was evaluated using test Shapiro-WilkЃfs W test. A statistically significant difference was considered at p.0,05. In acute experiments on male rats it was found that 2.2,5 hours after the administration of testosterone propionate (0,7 mg/kg, intraportal) significantly are reduced the concentration of phospholipids (at 25,02 % (p<0,01) compared to control), cholesterol (at 23,57 % (p<0,001) compared to control) and its ethers (at 35,65 % (p<0,001) compared to control) and free fatty acids (28,95 % (p<0001) compared to control samples). In these male rats bile samples the concentration of triglycerides is significantly higher (at 22,73 % (p<0,01)) than in the control. Efficiency of the used testosterone propionate dose at the exocrine function of male rat liver appeared gradually and only after 2.2,5 hours were found significant changes in the ratio of the major bile lipid fractions. Due to the widespread use of the testosterone propionate and given the detected its effects on lipid composition of bile after a single administration advisable to investigate the effect of a course of this hormone on the lipid secretory function of the liver.
The Ration of the Major lipid Fractions in the Bile of Rats with Testosterone Action
Keywords: тестостерон; печінка; ліпіди; жовч; testosterone; liver; lipids; bile